Ganadería en suelos ácidos : mejorar la productividad con especies forrajeras tolerantes (2016)
ABSTRACT: Agroecological conditions in tropical areas make acid and low fertility soils the most predominant in those regions. This kind of soils is the result of natural phenomena, like rain, or inadequate use of nitrogen fertilizers and inappropriate soil preparation practices. Soil management is particularly expensive in these areas, for crop establishment, because of their high dependence of external inputs to reach a moderated productivity level. The aim of this article is to explore new production alternatives, based in sustainability and profitability for livestock in acid soil areas, specifically grasses and forages with high tolerance to acidic and low fertility soils. It is expected that this information provides to technicians and owners a new perspective for acid soil management and new alternatives to reach high productiveness decreasing external input dependence.